2022
DOI: 10.32503/cendekia.v4i1.2332
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Urban Farming untuk Ketahanan Pangan di Wilayah RW VI Kelurahan Jatimulyo Malang

Abstract: Pekarangan di wilayah RW VI Kelurahan Jatimulyo Malang belum banyak yang dimanfaatkan untuk menanam tanaman secara produktif dan ekonomis. Program pengabdian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan ibu rumah tangga dalam budidaya sayuran organik sehingga meningkatkan ketahanan pangan di wilayah tersebut. Metode yang digunakan Program pengabdian masyarakat ini meliputi tahap pengenalan, tahap pelaksanaan dan tahap evaluasi program. Hasil kegiatan pelatihan urban farming di wilayah RW VI Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Examples include spinach, kale, basil, celery, mustard greens, cabbage, and lettuce. Fruit vegetables include eggplant, chili, cucumber, bitter gourd, chayote, winged, long, and green beans (Murwani et al, 2022). Meanwhile, tubers are whose roots are used (Rosdiana et al, 2023).…”
Section: Literature Review Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include spinach, kale, basil, celery, mustard greens, cabbage, and lettuce. Fruit vegetables include eggplant, chili, cucumber, bitter gourd, chayote, winged, long, and green beans (Murwani et al, 2022). Meanwhile, tubers are whose roots are used (Rosdiana et al, 2023).…”
Section: Literature Review Food Securitymentioning
confidence: 99%
“…For example, a preliminary study found that urban agriculture can improve food access and distribution in low-income communities (Atasa & Nugroho, 2021;Giriwati et al, 2018;Kamil & Romadhan, 2020;Nasuiton, 2020;Okuputra et al, 2022). Additional studies have investigated the role of urban agriculture in increasing equity of access to healthy food, examined the economic life of smallholder farmers, and addressed challenges in sustainable agriculture (Arifah & Poerbaningtyas, 2023.;Artandio et al, 2019;Ilham Pradana;& Wandari, 2023;Murwani et al, 2022;Setiyo et al, 2023). Moreover, poverty is a complex problem requiring a deeper understanding of exploitation and exploration to meet community needs.…”
Section: Introductionmentioning
confidence: 99%
“…Urban farming atau pertanian perkotaan merupakan salah satu solusi untuk masyarakat dalam mengolah lahan terbatas untuk dioptimalisasikan dan menghasilkan hasil pertanian bernilai jual tinggi. Selain itu, urban farming juga merupakan salah satu solusi untuk mencapai ketahanan pangan secara mandiri di lingkungan masyarakat perkotaan (Murwani et al, 2022). Pertumbuhan ekonomi nasional yang dimulai dari kelompok masyarakat kecil seperti UMKM dapat memberikan efek keberlangsungan yang panjang (Sarasmitha et al, 2022) Penggunaan metode urban farming juga terbukti dapat meningkatkan lahan terbuka hijau di area perkotaan yang padat penduduk (Santoso & Widya, 2014).…”
Section: Pendahuluanunclassified